Crucial factors for improving the ISO 14001 environmental management system - Ejdys, Joanna; Matuszak-Flejszman, Alina; Szymanski, Michał; Ustinovichius, Leonas; Shevchenko, Galina; Lulewicz-Sas, Agata (Journal of Business Economics and Management, 2016)
The practice of using environmental management systems (EMS) ISO 14001 at the organisational level indicates that the efficacy of such solutions depends on many factors, both endogenous and exogenous in nature. This article aims to identify the fac- tors that determine the opportunities for the improvement of EMS in organisations, the analysis of the relationship between the factors and the classification of the factors due to their role in the system improvement. The structural analysis was used to classify and identify the key factors and then to categorize these factors into five groups. Finally, the role of these key factors in improving environmental management systems was exam- ined. Based on the findings, guidelines can be offered to both scholars and practitioners regarding the factors crucial for the improvement of the EMS. Aiming to add value to the existing literature, the structural analysis was adapted to classification and identification of the key factors. From the point of view of practitioners, it seems to be very profitable to concentrate on the crucial factors during the process of EMS improvement.